The incidence and severity of poverty in New Zealand, 1990 -1991 - Stephens, Bob (School of Management Working Papers, 1994)
This paper reports on the findings on the incidence and severity of poverty in New Zealand for one year, 1990-91. It is based on the methodology set out in a companion paper (Stephens, 1994a), and will link in with a third paper which will look at the changes in the incidence and severity of poverty between 1982 and 1993. The year was chosen as being reasonably neutral in relation to the likely impacts of policy on the poor, and provided an opportunity to sort out many of the statistical difficulties in the measurement of poverty. Reporting on the data for one year will allow the reader to gain an understanding of the many different ways that the poverty data can be presented. Whilst the researchers on the project have a preference for the 60 percent of median equivalent household expenditure as their poverty measure (Stephens, Frater and Ward, 1992), the problems, theoretical limitations and methodological shortcomings inherent in that measure are recognised (Stephens, 1994b). The presentation of information on eight, interrelated measures of poverty may sometimes confuse the reader with a welter of statistics. The information provides readers with additional information on the nature and extent of poverty, as well as permitting them to use their own measure of poverty.